A new species of Microtityus Kjellesvig-Waering (Scorpiones: Buthidae) from northern Colombia - Botero-Trujillo, Ricardo; Erazo-Moreno, Martha C.; Pérez, Gustavo A. (Zootaxa, 2009)
Microtityus bivicentorum sp. nov. is described based on two adult specimens of both sexes from a single locality near the city of Valledupar, northern Colombia. The new species is most similar to Microtityus desuzeae González-Sponga, 2001 and Microtityus joseantonioi González-Sponga, 1981 from Venezuela, and Microtityus franckei Botero-Trujillo & Noriega, 2008 from Colombia, with which it shares the absence of trichobothrium d 2 on femur, Eb 3 and Esb on pedipalp chela, and esb on fixed finger. With this description, the number of extant species of Microtityus is raised to 25, of which eleven are present in South America and two in Colombia. A map with the known distribution of M. bivicentorum sp. nov. and similar species is presented. Some remarks about the trichobothrial arrangement of M. joseantonioi are also included.